2019
DOI: 10.11609/jott.4604.11.6.13680-13689
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and abundance of rodents in Kafta-Sheraro National Park, Ethiopia: preliminary results

Abstract: An ecological survey was conducted to assess the species composition and abundance of rodents in Kafta-Sheraro National Park, Ethiopia from June 2017 to April 2018 covering wet and dry seasons.  Rodents were trapped using Sherman live traps from five selected habitat types—natural forest, bushland, grassland, farmland, and human settlement.  A total of 209 individuals of rodents belonging to seven species were captured over 2940 trap nights, and three species of rodents were only observed.  The trapped rodent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
5
3
1
Order By: Relevance
“…In this study, during both seasons, the abundance of adult small mammals was higher than the number of sub-adult and young small mammals. This is in agreement with the studies of Redwan Mohammed et al (2017) and Alembrhan Assefa and Srinivasulu (2019), where capturing of more adult small mammals may be associated with their body size making it suitable for trappings or adults may have higher smelling capacity to human induced food items such as mixed peanut butter bait, as well as utilization of relatively larger home ranges.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, during both seasons, the abundance of adult small mammals was higher than the number of sub-adult and young small mammals. This is in agreement with the studies of Redwan Mohammed et al (2017) and Alembrhan Assefa and Srinivasulu (2019), where capturing of more adult small mammals may be associated with their body size making it suitable for trappings or adults may have higher smelling capacity to human induced food items such as mixed peanut butter bait, as well as utilization of relatively larger home ranges.…”
Section: Discussionsupporting
confidence: 91%
“…From the 10 documented species, M. natalensis wa s numerically the most abundant and widely distributed species. Similar results were reported by Datiko et al (2007); Bantihun and Bekele (2015) and Assefa and Srinivasulu (2019a). In the study area, high population of M. natalensis was recorded in farmland habitat.…”
Section: Discussionsupporting
confidence: 90%
“…This might be associated with the presence of food availability and the decline of natural predators due to human pressure. According to Byrom et al (2014Byrom et al ( , 2015 Similar results were reported by Datiko et al (2007); Bantihun and Bekele (2015) and Assefa and Srinivasulu (2019a). In the study area, high population of M. natalensis was recorded in farmland habitat.…”
Section: Ta B L Esupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, this study observed an increase in the number of adults in the burned area. This may be due to their larger home range, more active movement, and higher social ranking as identified by Assefa & Srinivasulu (2019). A decrease of subadults in the burned fields could be argued to be due to decreased vegetation and predation.…”
Section: Discussionmentioning
confidence: 95%